Effect of wearing helmet on traffic noise-induced health issues of motorcycle riders. (December 2022) - Das, Chidananda Prasad; Goswami, Shreerup; Swain, Bijay Kumar; Das, Mira
Abstract: Introduction: Transportation noise is a major source of concern in urban areas. Motorcycle riders, on the other hand, are the most exposed to traffic noise while riding. This study was carried out on 363 respondents (no-helmet: 121 respondents, half-face helmet: 121 respondents, and full-face helmet: 121 respondents) who were exposed to traffic noise while riding their motorcycles on the same noisy route, having the same exposure hours. The purpose of this study was to determine whether wearing a helmet protects against various traffic noise-induced psychophysiological health issues. It also tried to determine whether the riders were more affected than the pillion riders as a result of traffic noise exposure. Method: The psychophysiological factors of the respondents, such as annoyance, tiredness, depression, headache, and sleeping problem, were obtained using a standard questionnaire in accordance with ISO 15666, Beck et al. (1961), and Eriksen et al. (1999), respectively. The effect of wearing a helmet on traffic noise-induced psychophysiological reactions was investigated using structural equation modelling. Results: SEM route analysis revealed these significant relationships: (i) helmet use and gender (p-value: 0.017), (ii)) helmet use and marital status (p-value: 0.043), (iii) riders/pillion-riders and annoyance (p-value: < 0.001), (iv) riders/pillion-riders and gender (p-value: < 0.001). It was also observed that motorcyclists suffer from higher traffic noise-related health issues than pillion riders. SEM analysis further revealed that use of helmet can negatively affect the traffic noise induced annoyance, tiredness, depression, headache, and sleeping problem. Paired test data shows that there are significant differences in traffic noise induced annoyance level, tiredness, headache, depression, sleeping problems, and equivalent noise level. Conclusion: The use of a full-face helmet protects motorcyclists against a variety of traffic noise-related health problems. Practical implications: This study presents a thorough overview of the benefits of wearing a helmet against traffic noise pollution. Highlights: Effectiveness of helmet against traffic noise induced health effects are explored. A full-face helmet is beneficial to both physiological and psychological wellbeing. Motorcycle Riders are more vulnerable to traffic noise than pillion riders.